Novel Benzimidazole Derived Imine Ligand and Its Co(III) and Cu(II) Complexes as Anticancer Agents: Chemical Synthesis, DFT Studies, In Vitro and In Vivo Biological Investigations - Prakasha G; H. D. Revanasiddappa; Jayalakshmi B; Prabhakar B. T; Chandan Shivamallu; Prashant M. Viswanath; Raghu Ram Achar; Ekaterina Silina; Victor Stupin; Natalia Manturova; Ali A. Shati; Mohammad Y. Alfaifi; et al. (Pharmaceuticals, 2023)
The emerging interest in the field of coordination chemistry and their biological applications has created a novel impact in the field of chemical biology. With this motivation, in this work we have synthesized a novel benzimidazole derived imine ligand, 2-((E)-((1H-benzo[d]-2-yl)methylimino)methyl)-4-fluorophenol (HBMF) and its Co(III) and Cu(II) complexes. The metal complexes (C1–C4) were synthesized in 2:1 (HBMF: metal ion) and 1:1:1 (HBMF: metal ion: 1,10-phen) ratios. Structural elucidations of all the synthesized compounds were performed using FT-IR, UV-Visible, NMR, Mass spectroscopy and elemental analysis techniques. A combination of first principles calculations and molecular dynamics simulations was applied to computationally investigate the structural, reactive, and spectroscopic properties of the newly synthesized HBMF ligand and its complexes with copper and cobalt metal ions. Quantum-mechanical calculations in this study were based on the density functional theory (DFT), while molecular dynamics (MD) simulations were based on the OPLS4 force field. The DFT calculations were used to obtain the reactive and spectroscopic properties of the ligand and its complexes, while molecular dynamics (MD) simulations were used to address the ligand’s reactivity with water. Further, the in vitro anti-proliferative activity of the compounds was tested against the A549, Ehrlich–Lettre ascites carcinoma (EAC), SIHA and NIH3T3 cell lines. The biological results depicted that the compound C4, with molecular formula C27H23Cl2CoFN5O3 exhibited profound anti-proliferative activity against the EAC cell line with a significant IC50 value of 10 µm when compared to its parent ligand and other remaining metal complexes under study. Various assays of hematological parameters (alkaline phosphate, creatinine, urea, RBC and WBC) were performed, and significant results were obtained from the experiments. Furthermore, the effect of C4 on neovascularization was evaluated by stimulating the angiogenesis with rVEGF165, which was compared with non-tumor models. The EAC cells were cultured in vivo and administrated with 50 and 75 mg/kg of two doses and tumor parameters were evaluated.